Diel variation of the RNA/DNA ratios in Crassostrea angulata (Lamarck) and Ruditapes decussatus (Linnaeus 1758) (Mollusca : Bivalvia) - Chícharo, Luís (2013)
The aim of the present study was to quantify differences in RNA:DNA ratios between male and female fish Pomatoschistus microps, crustaceans Crangon crangon, and bivalves Ruditapes decussatus. RNA:DNA ratios were greater in females than in males, especially because of a greater RNA content per unit dry weight in females. Sexual dimorphism in addition to physiological and behavioural differences between males and females may account for these results. RNA:DNA ratios of adult marine organisms should be interpreted with caution, because the effect of sex on nucleic acid concentrations may bias results if the sex ratio in the sample from which results were derived is not representative of the population.